EFL POSTGRADUATE STUDENTS’ CRITICAL THINKING BELIEFS AND THEIR ABILITY IN WRITING RESEARCH METHODOLOGY - Arima Azwati; Slamet Setiawan; Oikurema Purwati (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2022)
The need to think critically is essential in this era and people must be competent in analyzing, evaluating, and problem-solving to stay afloat. This study aims to know the level of postgraduate students' critical thinking beliefs and their performance in writing the research methodology section of the research proposal. The study was a mixed-method study in which the quantitative method was applied to calculate the level of critical thinking belief by using a questionnaire, and qualitative data to analyze the draft of postgraduate students’ writing.  The questionnaire was distributed to the participants (five EFL postgraduate students), and documentation of their final project was collected. The study found that the EFL postgraduate students’ critical thinking beliefs were on the level of valuing and less on confidence in critical thinking. The level of valuing critical thinking meant EFL postgraduate students realized that critical thinking is a crucial ability they should master. However, they cannot implement it consistently for their study or social problems in daily life. The result of the content analysis of writing (research methodology) varies widely: some students were proficient in communication and problem-solving, and some were not, and synthesizing abilities became the lowest achievement of students' skills in writing.